(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Competitiveness is the main characteristic that leads oriented firms in their location choices. The new economy based on innovation and implicit knowledge has close ties to space that stimulates innovation and the transfer of knowledge assets for keeping competitiveness. To sustain the process of innovation; it demands continuity of transferring of knowledge (intangible) and (tangible). The current research discusses the catalysts that the urban ocean context can provide to stimulate innovation in industries. Many studies showed that there is level of successful relation between clusters and urban and regional contexts as they interacted differently. Many industrial clusters in Iraqi cities suffer from issues in interacting with their surroundings. This research aims to discuss the role of site quality in enhancing the appeal of innovation clusters. What are the planning characteristics of these clusters? This issue will be discussed according to the review of the literature, and the analysis of studies of innovation clusters and urban context indicators. The research aims to introduce a model to assist the process of evaluation of urban context according to its drivers to integrate with certain types of innovation clusters. The hypothesis is that spatial model [UCIS] can provide guides for spatial policy for developing innovation dynamics. The research methodology contains the following steps; put the research terms and definitions, define types of innovation clusters, and build a framework (territorial innovation model framework) that gives indicators of planning aspects that fulfill innovation needs. Inductive results from the case study will assist in identifying and categorizing precise effective indicators as the conceptual framework. elucidates the basic characteristics of site quality for establishing or promoting innovation clusters for Al-Exandria city in Iraq. The main conclusion of the study is that the model of [UCIS] can be a method that assists in determining the various policies of interference in cities according to aspects and levels of integration.